Exploring EFL Students' Perceptions of Linking Words in Writing: A Case Study at Bali International Language Center - Asriyani, Retny; Lindawati, Ni Putu; Anggayana, I Wayan Agus (LPPM Universitas Dhyana Pura, 2025)
This study explores EFL students' perceptions of linking words in writing at Bali International Language Center (BILCEN). Linking words, essential tools for achieving coherence and cohesion in writing, are often a challenge for EFL learners. This research aims to gain a deeper understanding of how students perceive the importance of linking words and how their use influences their writing skills. A qualitative approach was employed, with 15 EFL students enrolled in the English course at BILCEN as participants. Data were collected through semi-structured interviews and writing samples, which allowed for an exploration of students' personal experiences, thoughts, and challenges when using linking words in their written work. The analysis of interview responses and writing samples revealed that students recognized the significance of linking words in making their writing clearer and more organized. However, many students expressed challenges in using them correctly, often due to limited exposure or understanding of their varied functions. The findings suggest that while linking words are essential for enhancing writing coherence, students may benefit from more focused instruction and practice in using these words effectively. This research highlights the need for EFL programs to prioritize teaching linking words as part of developing students' writing proficiency.